2022
DOI: 10.3390/genes13101830
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Provides Insights into the Differential Effects of Aluminum on Peanut (Arachis hypogaea L.)

Abstract: In acidic soils, high concentrations of aluminum ions (Al3+) in dissolved form reduce root growth and development of most crops. In addition, Al3+ is also a beneficial element in some plant species in low concentrations. However, the regulatory mechanism of the growth and development of peanut (Arachis hypogaea L.) treated with different concentrations of Al3+ has been rarely studied. In this study, peanut seedlings were treated with AlCl3.18H2O in Hoagland nutrient solution at four different concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…According to the transcriptome findings, it was found that several TF families, namely, NAC , BHLH , WRKY , and MYB , which included differentially expressed TFs, performed a strong relationship between As100Glu0 and As100Glu100 (Figure f). These TF families were reported to be related to 2-AP biosynthesis pathway of fragrant rice , and environmental stress of plants. , Particularly, WRKY69, a member of WRKYs was significantly regulated by Glu supplementation in the study which was to construct the root architecture of rice, promoting root development . In addition, WRKY39 , which played a positive role in enhancing salinity tolerance by up-regulating CAT , APX , and GST , was reported .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…According to the transcriptome findings, it was found that several TF families, namely, NAC , BHLH , WRKY , and MYB , which included differentially expressed TFs, performed a strong relationship between As100Glu0 and As100Glu100 (Figure f). These TF families were reported to be related to 2-AP biosynthesis pathway of fragrant rice , and environmental stress of plants. , Particularly, WRKY69, a member of WRKYs was significantly regulated by Glu supplementation in the study which was to construct the root architecture of rice, promoting root development . In addition, WRKY39 , which played a positive role in enhancing salinity tolerance by up-regulating CAT , APX , and GST , was reported .…”
Section: Discussionmentioning
confidence: 91%
“…These TF families were reported to be related to 2-AP biosynthesis pathway of fragrant rice 1,49 and environmental stress of plants. 45,50 Particularly, WRKY69, a member of WRKYs was significantly regulated by Glu supplementation in the study which was to construct the root architecture of rice, promoting root development. 35 In addition, WRKY39, which played a positive role in enhancing salinity tolerance by upregulating CAT, APX, and GST, was reported.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Interestingly, the plant hormone signaling pathway was significantly upregulated at higher concentration of Aluminium treatments. Furthermore, the expression of transcription factors (TFs) in peanut is concentration dependent and overall, this study showed that Al at low concentration acts as a stimulant, while at high concentration it is toxic and acted as an inhibitor (Bao et al, 2022a).…”
Section: Cold and Metal Stressmentioning
confidence: 86%
“…In recent years, RNA sequencing (RNA-seq) has emerged as an indispensable tool for transcriptome analysis because it can generate a vast number of reads, providing a comprehensive overview of the transcriptomic landscape. Consequently, RNA sequencing has been applied to investigate Al response mechanisms in various plant species, including Pinus massoniana [42], sugarcane [43], aspen [44], peanut [45], and alfalfa [46], uncovering numerous physiological and metabolic processes involved in Al stress such as oxidative stress, organic acid exudation, defense against cell wall toxicity, and hormone signal transduction. Despite extensive information on Al stress responses, the specific mechanisms via which melatonin regulates Al toxicity in alfalfa remain unexplored.…”
Section: Of 17mentioning
confidence: 99%